2009
DOI: 10.7589/0090-3558-45.3.834
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Snaring by Ingested Fishing Net in a Common Bottlenose Dolphin (Tursiops truncatus) Off the Israeli Shoreline

Abstract: We report an unusual snaring of the larynx in an adult, female common bottlenose dolphin (Tursiops truncatus). The dolphin was observed swimming and diving in Haifa Port, Israel, but was found dead the next day, 60 km south, on the coast. Postmortem examination revealed stranded-cordage, nylon filaments wrapped around the larynx, cutting through the soft tissue, and extending down into the forestomach, where a large mass of netting was found. The cachectic state of the dolphin and the subacute to chronic, hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…Litter ingestion (%) Levy et al (2009) of macroplastics by large predatory fishes in subsurface waters (Choy and Drazen, 2013). Again, more focus should be placed on organisms inhabiting layers other than surface waters because the magnitude and extent of litter in these areas have been underestimated worldwide.…”
Section: Speciesmentioning
confidence: 99%
“…Litter ingestion (%) Levy et al (2009) of macroplastics by large predatory fishes in subsurface waters (Choy and Drazen, 2013). Again, more focus should be placed on organisms inhabiting layers other than surface waters because the magnitude and extent of litter in these areas have been underestimated worldwide.…”
Section: Speciesmentioning
confidence: 99%
“…The method as defined above can be beneficial in dolphins with suitable size. On the other hand, Levy et al (2009), made use of a laryngeal snare in the removal of a fishnet swallowed by a bottlenose dolphin. Greenwood et al (1978), reported that removal of foreign bodies in dolphins can be performed by using various grasping forceps pushed forward down the work channel via use of a fiberscope.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Arctic ground squirrels Spermophilus parryii plesius in poor and excellent body condition had similar d 15 N values (Ben-David et al, 1999) and muscle and d 13 C values did not differ between porpoises from the North Sea displaying poor, moderate and good body condition (Das, 2002). In the present study, an adult dolphin with very poor physical body condition (Levy et al, 2009) had the lowest d 15 N. As noted above, it is assumed that the majority of the sampled dolphins were healthy by-caught victims. Another potential confounding effect, the possible change of d 15 N during the decay process of a beached animal, has recently been shown not to exist (Payo-Payo et al, 2013).…”
Section: Stable Isotopesmentioning
confidence: 97%